Adjuvant radiotherapy in early stage endometrial cancer - Zuliani,Antonio Carlos (2011)
OBJECTIVE: To compare the rates of overall survival (OS), disease-free survival (DFS) and toxicity in different techniques of postoperative radiotherapy for stage IA endometrioid adenocarcionoma of endometrium, histological grades 1and 2. METHODS: A historical comparison between treatment regimens was performed, and 133 women with a minimum follow-up of 5 years were included. Teletherapy (TELE group), with 22 patients treated from 1988 to 1996, with a 10 MV linear accelerator, average dose 46.2 Gy. Low dose rate brachytherapy (LDRB group) was performed between 1992 and 1995, in 19 women, with an insertion of Cesium 137, at a 60 Gy dose. Fourteen women operated between 1990 and 1996 did not receive radiotherapy (NO RT group). High dose rate brachytherapy was performed in 78 patients (HDRB group), from 1996 to 2004, in five weekly 7 Gy insertions, prescribed at 0.5 cm from the vaginal cylinder. RESULTS: The 5-year disease-free survival was 94.6% for the HDRB group, 94.1% for the LDRB group, 100% for the TELE group and NO RT groups (p = 0.681). The 5-year overall survival was 86.6% for the HDRB group, 89.5% for the LDRB group and 90% for the TELE group and NO RT groups (p = 0.962). Grades 3-5 late toxicity was 5.3% in LDRB group and 27.3% for the TELE group (p < 0.001). CONCLUSION: Patients submitted to adjuvant teletherapy showed very high toxicity, which contraindicates that treatment for those patients. There may be a role for adjuvant HDRB, but randomized controlled trials are still needed to evaluate its benefit.